Analysis of the collagen VI assemblies associated with Sorsby's fundus dystrophy. - Knupp, C; Chong, N; Munro, P; Luthert, P; Squire, J (2002)
Age-related macular degeneration is the leading cause of blindness in the Western world, and the pathophysiology of the condition is largely unknown. However, it shares many clinical and pathological features with Sorsby's fundus dystrophy (SFD), an autosomal dominant disease, known to be associated with mutations in the TIMP-3 gene. In Bruch's membrane of both conditions, there are molecular assemblies with distinct transverse bands occurring with a periodicity of about 100 nm. Similar assemblies were also found in the vitreous of a patient with full-thickness macular holes and were identified as being made of collagen VI. The assemblies found in the eye with SFD can be classified into two types, both with a 105-nm axial repeat, but one showing pairs of narrow bands about 30 nm apart and the other showing a single broad band in every repeat. By comparison with the assemblies in the vitreous, collagen VI is considered to be the most likely protein in these assemblies. Furthermore, both of the assemblies associated with SFD can be explained in terms of collagen VI tetramers, one in which the tetramers bind to the mutant tissue inhibitor of metalloproteinases-3 (the gene product of TIMP-3) and the other in which little or no binding occurs. TIMP-3 bound to collagen VI may be more resistant to degradation and create an imbalance between the normal amount of TIMP-3 and matrix metalloproteinases (the substrate of TIMPs) in Bruch's membrane with consequent disruption of the normal metabolic processes. Understanding the structure of these collagen VI/TIMP assemblies in Bruch's membrane may prove to be important for understanding the pathophysiology of age-related macular degeneration.